The “Cascade” membrane: a new PRP device for tendon ruptures.Description and case report on rotator cuff tendon - Maniscalco, P.; Gambera, D.; Lunati, A.; Vox, et al., G. (Acta Biomedica Atenei Parmensis, 2008)
Rotator cuff tears are common soft-tissue injuries that often require surgical treatment. Initial efforts to better tendon healing centered on improving the strength of repair. More recent studies have focused on abiologic enhancement of the healing process. Platelet rich plasma (PRP) is a fraction of plasma that has been isolated and used to enhance regeneration in bone and soft tissues. The healing potential of PRP has been attributed to the release of multiple growth factors from the highly concentrated platelets. The “Cascade” membrane is a thin layer of autologous fibrine that is very rich in platelets and is obtained by high speed centrifugation of a small quantity of PRP. The Authors present the case of C.U., a  right-handed 53year-old male that came to our attention complaining of severe right shoulder pain and ROM reduction. The MRI showed a thick tear of the sovraspinatus tendon with retraction of the muscle. The patient underwent surgical repair with arthroscopy and mini-open approach with acromionplasty, subacromial decompression, cuff repair by trans-bone suture and application of the “Cascade” membrane (A.T. Grade Milano, Italy) that was sutured side-to-side to close the 10 mm tear. A standard rehabilitation protocol for rotator cuff tears was performed. A MRI 6 months after surgical repair showed the complete integrity of the cuff under the membrane. Currently no widely accepted treatment for massive, irreparable rotator cuff tears is available. Allograft reconstruction to span the remaining defect in massive rotator cuff tears will lead to increase functional results; we believe that further studies are needed to describe and evaluate its potential in tendon healing; multiple MRI studies will demonstrate healing of the tendon with the graft.